Genetic variability of carotenoids and polypoid induction towards vitamin A biofortification in plantain (Musa spp.) - Amah, Delphine (University of the Free State, 2018)
Vitamin A deficiency (VAD) is one of the most prevalent nutrient deficiencies affecting the health of resource-poor populations in developing countries. Plantains (Musa spp. AAB) are a specific group of bananas, which serve as a staple for millions of people in the humid lowlands of West-Central Africa and high provitamin A carotenoid (pVAC) plantain varieties, could have significant impact on VAD in these regions. In this regard, the International Institute of Tropical Agriculture (IITA) based in Nigeria, is developing a breeding pipeline aiming to generate and deploy plantain hybrids combining high pVAC content with other consumer-preferred traits. The overall objective of this study was therefore to assess the variability of fruit pVAC content in banana cultivars and hybrids present in the collection of IITA, Nigeria, and investigate the potential of induced polyploidization as a breeding approach towards plantain biofortification. A wide collection of 204 genotypes of bananas (AAB-plantains, M. acuminata cultivars and bred hybrids) was screened to determine variability in fruit pVAC content using high- performance liquid chromatography (HPLC) and spectrophotometry. Mean total carotenoids (TC) measured by spectrophotometry ranged from 1.28 to 32.03 with a mean of 8.88 μg g-1 fresh weight (FW) indicating a high variability of carotenoids in bananas. There was a strong correlation between TC measured by spectrophotometry and that estimated from HPLC, confirming the potential of spectrophotometry as a useful, inexpensive method for rapid screening for pVACs in banana. Predominant carotenoids isolated were α-carotene (38.67%), trans β-carotene (22.08%), lutein (22.08%), 13-cis-β- carotene (14.45%) and 9-cis β-carotene (2.92%), demonstrating that about 78% of the carotenoids in bananas are pVACs. Provitamin A content estimated in terms of β-carotene equivalents (BCE) ranged from 0.24 to 21.06 μg g-1 FW with a mean value of 4.42 μg g-1 FW across all genotypes. Importantly, 10 plantain cultivars, three M. acuminata diploids and four hybrids with relatively high pVAC contents were selected for integration in banana biofortification efforts to tackle VAD. To assess the effect of ripening on pVACs in plantain fruits, nine cultivars across the three main plantain types (French, False Horn and Horn) were screened at the unripe, ripe and overripe stage. Mean TC measured by spectrophotometry for plantain cultivars at the unripe, ripe and overripe stage was 16.94, 11.98 and 10.11 μg g-1 FW while mean BCE was 13.65, 6.95 and 5.05 μg g-1 FW, respectively. Notably over 80% of carotenoids in plantain cultivars were pVACs α-carotene and β-carotene across all ripening stages. French plantains had slightly higher BCE contents than False Horn and Horn types but this difference was only significant (P<0.05) at the unripe stage. Overall, ripening led to a decrease in pVACs content from the unripe to the ripe to the overripe stages accompanied by a corresponding increase in lutein content indicating that unripe fruits could yield more provitamin A than ripe and overripe fruits. To explore the application of induced polyploidization as a breeding strategy for pVAC enhancement in plantains, 10 induced tetraploids derived from six diploid cultivars were evaluated for their agronomic attributes, carotenoid content and fertility. Tetraploids had distinct plant morphology but generally displayed inferior vegetative and yield traits from their corresponding diploids. Similarly, a 50% decrease in pVACs accompanied by a corresponding increase in lutein was recorded in induced tetraploids in comparison to their original diploids. Nevertheless, preliminary fertility assessments indicated over 70% pollen viability for induced tetraploids from four diploid cultivars. These findings demonstrated the use of induced polyploidization to generate useful genetic material that could be incorporated in hybridization programmes aiming to produce high pVAC triploids.
Thesis (Ph.D. (Plant Sciences))--University of the Free State, 2018
Keywords: Biofortification; Breeding; Fruit ripening; High performance liquid chromatography; Induced polyploidization; Musa spp; Plantain; Pollen viability; Provitamin A carotenoid; Spectophotometry; Vitamin A deficiency